Identification of main contamination points by hygiene indicator microorganisms in beef processing plants - Barros, Márcia de Aguiar Ferreira (2007)
The microbiological quality of beef and meat products is strongly influenced by the conditions of hygiene prevailing during their production and handling. Without proper hygienic control, the environment in slaughterhouses and butcher shops can act as an important source of microbiological contamination. To identify the main points of microbiological contamination in the beef processing chain, 443 samples of equipment, installations and products were collected from 11 establishments (1 slaughterhouse and 10 butcher shops) located in the state of Paraná, Brazil. The microbiological quality of all the samples was evaluated using Petri dishes to obtain counts of mesophilic aerobes (AC), total coliforms, Escherichia coli (EC), yeasts and molds (YM). The main contamination points identified in butcher shops, in decreasing order, were stainless steel boxes, beef tenderizers, grinders, knives, mixers, sausage stuffers, plastic boxes, floors and drains. In the slaughterhouse, these points were sausage stuffers, platforms, floors and drains. The most severely contaminated products were fresh sausages and ground beef. This information about the main points of microbiological contamination in the beef processing chain is expected to aid professionals responsible for hygiene in similar establishments to set up proper hygienic procedures to prevent or reduce microbiological contamination of beef and meat products.